Financial Services Trade in Special Economic Zones. (18th May 2021) - Delimatsis, Panagiotis
ABSTRACT: The mushrooming of special economic zones (SEZs) in recent years has led to a significant increase in the supply of attractive incentives for investors looking for opportunities abroad. Special economic zones are self-contained regimes, inextricably associated with investment promotion policies and domestic industrial policy in general, that many times form part of a broader strategic governmental planning that aims at experimenting with economic rule-making in strictly defined territorial and jurisdictional boundaries. While empirical evidence is still inconclusive, special economic zones can contribute to economic development at the domestic level through a varying degree of channels. This is even more the case with services-only special economic zones, a new phenomenon that exemplifies the rising importance of trade in services but also the 'servicification trend' that drives global economic activity. Against this background, this article examines the case of services in special economic zones and offers a tour d'horizon of the current services-related special economic zone landscape. Furthermore, the article critically reviews the patterns, traits, and limits of trade in financial services within special economic zones and discusses the relevance of the General Agreement on Trade in Services at this juncture. It concludes with a discussion of potential development-related benefits ensuing from trade in financial services within special economic zones.